KOMPLEKSITAS PEMERTAHANAN DAN REVITALISASI BAHASA MINORITAS DI INDONESIA: PENGALAMAN PROYEK DOKUMENTASI RONGGA, FLORES - I Wayan Arka (Masyarakat Indonesia, 2011)
This paper discusses complexities faced by the minority Rongga people in thecontext of language maintenance and revitalization, based on feld experiencein documenting the Rongga language. Issues in language maintenanceand revitalization are discussed from a range of macro-variables such ashistorical, socio-political, cultural, economic and sociolinguistic factors. It isdemonstrated that the Rongga case is a typical complex situation faced byminority ethnic groups in Indonesia who have been increasingly marginalizedin almost every aspect. The low capacity of maintaining their language/cultureis a result of a long and complex process which the people of Rongga haveexperienced. The effect is that internal and external support has been alwaysweak or absent. Internally, pride of own language/culture is always low; thefunction of traditional custom (adat) laws is signifcantly reduced; poverty iswidespread, and there are problems with local human resources. Externally,the Rongga people have been dominated by outsiders at all levels, includingat the local level. The introduction of the new Javanese-style village structurehas negatively affected the vitality of the Rongga people. In addition, Ronggalanguage is also under pressure from the national/regional language policy inIndonesia. The paper discusses the prospect and challenges ahead, and reportsthe activities undertaken in the feld work.Keywords: language maintenance, language revitalization, languagedocumentation, minority language, ethnic of Rongga, Flores